2022
DOI: 10.3390/ijerph19073976
|View full text |Cite
|
Sign up to set email alerts
|

A Citizen Science Approach to Identifying Indoor Environmental Barriers to Optimal Health for under 5s Experiencing Homelessness in Temporary Accommodation

Abstract: The first five years of life are critical for optimal growth, health, and cognitive development. Adverse childhood experiences, including experiencing homelessness, can be a risk factor for multiple health issues and developmental challenges. There is a dearth of data collected with and by families with children under age five living in temporary accommodation due to experiencing homelessness (U5TA) describing indoor environmental barriers that prevent U5TA from achieving and maintaining optimal health. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Both inductive and deductive coding were included, including theory-driven and data-driven codes [29,30]. An adapted socio-ecological model (SEM) [2,31] was used as a guiding theoretical framework.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both inductive and deductive coding were included, including theory-driven and data-driven codes [29,30]. An adapted socio-ecological model (SEM) [2,31] was used as a guiding theoretical framework.…”
Section: Methodsmentioning
confidence: 99%
“…Under 5s experiencing homelessness in temporary accommodation (U5TA) are particularly vulnerable to poor health outcomes and poor healthcare service access in comparison to the general population [1,2] due to their transient circumstances and lower visibility, unlike other groups experiencing homelessness, such as rough sleepers [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Singapore, 'homelessness' is defined as "any person found begging in a public place in such a way as to cause or be likely to cause annoyance to persons frequenting the place or otherwise to create a nuisance", [32] whereas in South Korea, it is defined as "persons who have used/lived homeless facilities for a substantial period". [33] As highlighted by Rosenthal et al(2021), the varying definitions of homelessness can have significant implications for the provision of mental health services depending on how it is recognised within a given jurisdiction, [34] and therefore, could act as a barrier to accessing mental health services. There is a lack of government policies that mention mental health services for this population based on those definitions [25] implying that mental health services are not adequately addressed by the government.…”
Section: Problems Of Defining 'Homelessness'mentioning
confidence: 99%
“…For instance, in the UK, a recent study found that 41 per cent of people experiencing homelessness reported a long-term physical health problem and 45 per cent had a diagnosed mental health problem, compared with 28 per cent and 25 per cent, respectively, in the general population [10]. Determining accurate national estimates of homelessness prevalence and health and social characteristics among people experiencing homelessness is difficult for many reasons, including the mobility of the population and a lack of standardised collection of homelessness status in national administrative healthcare data systems [11][12][13][14][15]. A number of record linkage and administrative data research studies [16][17][18][19] have been conducted in this area.…”
Section: Introductionmentioning
confidence: 99%